ANALISIS PENGARUH KUALITAS LAYANAN WEBSITE PT. KERETA API INDONESIA (PERSERO) TERHADAP KEPUASAN PENGGUNA DENGAN METODE WEBQUAL 4.0 - Leza Risti Navyca; Sulistiowati Sulistiowati; Tegar Heru Susilo (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
PT. KAI (Persero) has a website that addresses the www.kereta-api.co.id as part of its work in providing various facilities that can be used by customers. Facilities or services contained on this website include a company profile, product services of passengers and goods, news and press releases, company performance reports, awards, procurement, recruitment, and online reservation service. In this study, analysis activities about influence of the website quality of PT. KAI (Persero) to the user's satisfaction as perceived by end users and site visitors by using WebQual 4.0. The data collection is done by providing online and offline questionnaires to determine what services will be analyzed based on the indicators of WebQual. The results of the questionnaire data and then tested the validity, reliability, test assumptions Linear Regression testing requirements. Based on this study resulted in a conclusion that the quality of use (usability), the quality of information (information quality), and the quality of interaction (interaction quality) positive and significant impact on user satisfaction (user satisfaction) with the effect of 66.7%, the rest (100- 66.7%) = 33.3% influenced by other variables not examined. Keywords: Website Quality, User Satisfaction, Linear Regression.